Patient Perceived Involvement in Their Treatment is Influenced by Factors Other Than Independently Rated Clinician Communication Effectiveness. (January 2021) - van Rossenberg, Luke X.; Ring, David; Jacobs, Xander; Sulkers, George; van Heijl, Mark; van Hoorn, Bastiaan T.
We analyzed (1) the correspondence of patient and clinician perceived patient involvement in decision making and ratings made by independent observer's independent ratings, as well as (2), factors associated with patient-perceived involvement, among patients seeking hand specialty care. During 63 visits, the patient, their hand specialist, and 2 independent observers each rated patient involvement in decision making using the 9-item shared decision-making questionnaire for patients and clinicians, and the 5-item observing patient involvement scale (OPTION-5). We also measured health literacy (Newest Vital Sign), patient and visit characteristics (gender, age, race, years of education, occupation, marital status, and family present). There was no correlation ( ρ = 0.17; P = .17) between patient (median 42, IQR 36-44.5) and clinician (38, IQR 35-43) ratings of patient involvement in decision making. Independently rated patient involvement correlated moderately with specialist ( ρ = 0.35, P <.01), but not patient ( ρ = 0.22, P = .08) ratings. The finding that patient perception of their involvement in decision making has little or no relationship to independently rated clinician communication effectiveness and effort, suggests that other aspects of the encounter—such as empathy and trust—may merit investigation as mediators of the patient agency.